Estimation and evaluation of transport costs : Report of the one hundered and thirty sixth round table of transport economics - Round Table on Transport Economics 2005 : Paris, France); Transport Research Centre; European Conference of Ministers of Transport. Economic Research Centre (Paris : Organisation for Economic Co-operation and Development, 2007)
Cost data for the construction and operation of facilities are essential for the evaluation of infrastructure services supplied by private or public providers. This roundtable examines what data is needed for evaluation; which methods best measure the efficiency of service provision and benchmark providers; how regulatory regimes impact costs; and how regulators can counter the asymmetry of information as well as the incentive for data providers to selectively serve business rather than user interests.--Publisher's description.
Measuring inefficiencies in transport systems: between technology and incentives / by P. Gagnepain and M. Ivaldi -- Infrastructure maintenance costs: a comparison of road, rail and inland navigation, and implications for user charges / by P. Rietveld, F. Bruinsma and M. Koetse -- Technical efficiency in the Portuguese airports with a stochastic cost frontier model / by C. Barros -- Transport cost levels, productivity and efficiency measures: some theory and main policy uses / by A. Estache and L. Trujillo.
At head of title: Transport Research Centre
Includes bibliographical references
Keywords: Transportation -- Costs -- Congresses